Polityka bezpieczeństwa wewnętrznego gabinetów z udziałem Sojuszu Lewicy Demokratycznej - Sprengel, Bolesław (Polityka i Społeczeństwo, 2021)
The Democratic Left Alliance implemented an ambitious interior security policy in fighting with corruption and administrative modernization. This programme was only in part of a left-wing nature, but it was also the result of current needs. This program was controlled by journalists, who at times exaggerated its errors and failure.